Front Cover: Elucidating 2D Charge‐Density‐Wave Atomic Structure in an MX–Chain by the 3D‐ΔPair Distribution Function Method (ChemPhysChem 6/2022). Issue 6 (18th March 2022) - Guérin, Laurent; Yoshida, Takefumi; Zatterin, Edoardo; Simonov, Arkadiy; Chernyshov, Dmitry; Iguchi, Hiroaki; Toudic, Bertrand; Takaishi, Shinya; Yamashita, Masahiro
Abstract : The Front Cover illustrates that the atomic structure of a 2D charge density wave can be revealed although the planes associated to this local 2D order are randomly stacked preventing the use of conventional structure determination techniques. More information can be found in the Research Article by Laurent Guérin, Takefumi Yoshida and co‐workers .